2022
DOI: 10.1002/eji.202049067
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for standardizing T‐cell cytometry assays to link biomarkers, mechanisms, and disease outcomes in type 1 diabetes

Abstract: Cytometric immunophenotyping is a powerful tool to discover and implement T-cell biomarkers of type 1 diabetes (T1D) progression and response to clinical therapy. Although

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 105 publications
1
8
0
Order By: Relevance
“…From rested peripheral blood samples, we used six flow cytometry panels adapted from HIPC recommendations (13) as we previously published (18; 32), to generate detailed immunophenotyping data encompassing proportions of innate and adaptive immune cells as well as phenotypes of memory T cell, Treg, Teff, T follicular helper (Tfh), B cell, DC, monocyte, and NK cell subsets ( Figure 1A , with detailed gating schematics in Figures S1-S6 ). We first tested an initial cohort of 12 individuals in duplicate to evaluate assay reproducibility and observed that the biological coefficient of variance (CV) largely outweighed variance between technical duplicates (45.23 ± 25.66% vs. 8.87 ± 7.56%, Figure 1B ), in agreement with previously established guidelines for replicability in flow cytometric studies (33). These studies were then extended to characterize flow cytometric immunophenotypes with accompanying complete blood count (CBC) measurements, for a total of 192 total outcome measures, on a large cross-sectional cohort of n =826 persons with or at varying levels of risk for T1D ( Table 1 ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…From rested peripheral blood samples, we used six flow cytometry panels adapted from HIPC recommendations (13) as we previously published (18; 32), to generate detailed immunophenotyping data encompassing proportions of innate and adaptive immune cells as well as phenotypes of memory T cell, Treg, Teff, T follicular helper (Tfh), B cell, DC, monocyte, and NK cell subsets ( Figure 1A , with detailed gating schematics in Figures S1-S6 ). We first tested an initial cohort of 12 individuals in duplicate to evaluate assay reproducibility and observed that the biological coefficient of variance (CV) largely outweighed variance between technical duplicates (45.23 ± 25.66% vs. 8.87 ± 7.56%, Figure 1B ), in agreement with previously established guidelines for replicability in flow cytometric studies (33). These studies were then extended to characterize flow cytometric immunophenotypes with accompanying complete blood count (CBC) measurements, for a total of 192 total outcome measures, on a large cross-sectional cohort of n =826 persons with or at varying levels of risk for T1D ( Table 1 ).…”
Section: Resultssupporting
confidence: 80%
“…Samples were collected in ethylenediaminetetraacetic acid (EDTA)-coated vacutainer tubes for flow cytometry, complete blood count, HbA1c, TCRβ sequencing, and genotyping assays; serum separator vacutainer tubes for islet autoantibody and CMV IgG antibody measurement; and sodium fluoride/potassium oxalate-coated tubes (BD Biosciences) for rested blood glucose quantification, and stored in accordance with institutional review board (IRB)-approved protocols at each participating institution. Samples were shipped or rested overnight prior to flow cytometric staining in order to standardize duration between collection and evaluation at UF (33). Data were collected from all incoming blood samples to the UFDI from 2014-2018, hence the lack of age-matching between clinical subgroups based on clinical status.…”
Section: Methodsmentioning
confidence: 99%
“…This information will also guide subsequent approaches to therapeutic interventions. There are excellent recent reviews on factors impeding progress toward the development of effective T-cell biomarkers in T1D ( 52 , 98 , 99 ).…”
Section: Biomarkersmentioning
confidence: 99%
“…We anticipate that PBMCs from this study will be useful for flow cytometry or mass cytometry by time-of-flight studies for phenotypic and functional bulk characterization of circulating immune cells. [52][53][54] Importantly, PBMCs enable the measurement of antigen-specific T-cells specific for either endocrine or exocrine tissue, helping to define whether antigen specificity differs in the setting of the AP inflammatory insult compared with the well-described range of antigens detectable in typical T1D (recently reviewed in Refs. 55 and 56).…”
Section: Biobanking For the Future: Peripheral Blood Mononuclear Cellsmentioning
confidence: 99%